The structural prevention of mass atrocities understanding risk and resilience - McLoughlin, Stephen (Routledge studies in genocide and crimes against humanity, 2014)
"This book offers a different approach to the structural prevention of mass atrocities. It investigates the conditions that enable vulnerable countries to prevent the perpetration of such violence"